2022
DOI: 10.1111/acer.14913
|View full text |Cite
|
Sign up to set email alerts
|

Intake assessments of salivary cortisol, survey responses, and adverse childhood experiences are associated with recovery success in an abstinence‐based treatment program for substance use disorders

Abstract: Background: Connecting patients to treatment for a substance use disorder (SUD) that satisfies their needs is often complicated by confounding factors. A reliable measurement of patients' underlying stress level may be helpful because it often reflects many of the same confounders as their SUD. Whereas cortisol levels reflect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…We found that higher perceived stress during admission predicted shorter treatment retention. These findings may be attributable to different factors, including the stressful nature of recovery and clients’ inability to use substances to cope with this stress ( Maddox-Rooper et al, 2022 ). This study also found that individuals being of another race/ethnicity compared to being Non-Hispanic Black predicted premature discharge in this sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that higher perceived stress during admission predicted shorter treatment retention. These findings may be attributable to different factors, including the stressful nature of recovery and clients’ inability to use substances to cope with this stress ( Maddox-Rooper et al, 2022 ). This study also found that individuals being of another race/ethnicity compared to being Non-Hispanic Black predicted premature discharge in this sample.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals in this sample with higher perceived stress may have left treatment prematurely in response to their discomfort. Further, abstaining from substances during treatment and recovery is itself inherently stressful ( Maddox-Rooper et al, 2022 ). Changing patterns related to substance use is also stressful as it may cause different interactions with an individual’s environment after treatment discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, a recent study (Maddox‐Rooper et al, 2022) investigated relationships between salivary cortisol levels, stress exposure, adverse childhood experiences (ACEs), and completion of an abstinence‐based residential recovery program. The researchers hypothesized that decreased cortisol levels, less stress, and fewer ACEs would be associated with increased stay in the recovery program or program completion.…”
mentioning
confidence: 99%